2017
DOI: 10.1038/leu.2017.123
|View full text |Cite
|
Sign up to set email alerts
|

E-selectin ligands recognised by HECA452 induce drug resistance in myeloma, which is overcome by the E-selectin antagonist, GMI-1271

Abstract: Multiple myeloma (MM) is characterized by the clonal expansion and metastatic spread of malignant plasma cells to multiple sites in the bone marrow (BM). Recently, we implicated the sialyltransferase ST3Gal-6, an enzyme critical to the generation of E-selectin ligands, in MM BM homing and resistance to therapy. Since E-selectin is constitutively expressed in the BM microvasculature, we wished to establish the contribution of E-selectin ligands to MM biology. We report that functional E-selectin ligands are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 48 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…Thus, it is critical to establish a stratgegy for patient stratification and treatment scheduling (e.g., duration and administration sequence with chemotherapy). Given the pivotal role of E-selectin as a mediator of tissue migration and its spatiotemporally limited expression on the luminal surface of inflamed vessels, different chemical entities of antagonistic ligands have been developed [21,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is critical to establish a stratgegy for patient stratification and treatment scheduling (e.g., duration and administration sequence with chemotherapy). Given the pivotal role of E-selectin as a mediator of tissue migration and its spatiotemporally limited expression on the luminal surface of inflamed vessels, different chemical entities of antagonistic ligands have been developed [21,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ST3GAL4 is also upregulated in cancer, and is associated with poor prognosis; metastasis and the synthesis of Sialyl Lewix X (sLe X ) in gastric carcinoma [18,35]. ST3GAL6 is also linked to the synthesis of sLe X and the generation of E-selectin ligands [36,37]. Recently, ST3GAL6 was found to be critical to bone…”
Section: Glycosyltransferase and Glycosidase Enzymesmentioning
confidence: 99%
“…Similarly, ST3GAL4 is also upregulated in cancer, and is associated with poor prognosis; metastasis and the synthesis of Sialyl Lewix X (sLe X ) in gastric carcinoma [18,35]. ST3GAL6 is also linked to the synthesis of sLe X and the generation of E-selectin ligands [36,37]. Recently, ST3GAL6 was found to be critical to bone marrow homing and resistance to therapy in multiple myeloma [36], and a follow-up study demonstrated this can be inhibited with the E-selectin antagonist GMI-1271 [37].…”
Section: Glycosyltransferase and Glycosidase Enzymesmentioning
confidence: 99%
See 2 more Smart Citations